“Soja não dá na prateleira”: análise crítico-jurídica do modelo de desenvolvimento na ocupação do cerrado de Uruçuí - PI pelo agronegócio de soja, a partir da teoria da Amartya Sen - Santos, Adrianna de Alencar Setubal (2019)
The present thesis aims to analyze the development experience of the municipality of Uruçuí, located in the Southwest region of the state of Piauí which, due to its prominence in the national production scene, reveals a mismatch to be investigated, suggested by the peripheral position of Piauí in the Brazilian economic and social context. Therefore, the research problem is to explore the existence of the experience of development as an exercise of human capabilities proposed by Amartya Sen, specifically in the Cerrado region of Uruçuí, with soybean agribusiness. As a tentative answer to the problem, the research hypothesis was constructed in order to inform that the implanted productive model promotes economic growth, but not development, in the face of the identified human privations and to which the State intervened action would have contributed, deconstructing the constitutional commitment to national development. For the solution of the problem of research and verification of the hypothesis, the study starts from the multivocal configuration of the term development to define it as freedom, serving such delimitation as category of analysis of the concrete. The legal development is situated with the formulation of the right to development, human prerogative and fundamental that serves as an instrument. At the political level, planning and public policy are exposed to set the tone for state action and reveal the mode of action expected for development experience. Structured in a dialogical way, the thesis contrasts what was theorized with the empirical, the result of interviews, direct observation and analysis of normative texts and action plans produced by the state of Piauí, to perform the critical interpretative analysis of the extracted, conclude that lack of development in that region.